YouTube Videos as Supplementary Materials to Enhance Computer Troubleshooting and Repair Techniques for Senior High School Students in the Philippines - Caratiquit, Kevin (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
This study aimed to improve learners' academic performance in Computer Troubleshooting and Repair Techniques at Lal-lo National High School by using YouTube videos with teacher-made learning activity sheets as supplementary materials. The study employed a quasi-experimental design, particularly a one-group pretest and post-test design, in which the intervention was administered to the same participants. The result proved that the learners gained a higher mean on their post-test result than their pretest, indicating a significant difference between the pretest and post-test scores. Moreover, the intervention greatly affected the student's academic performance, particularly on the competency in Computer Troubleshooting and Repair Techniques. YouTube videos can help visual learners and students better understand a subject. These videos can catch students' imagination, especially when face-to-face learning is discouraged owing to the epidemic. The intervention material may be adapted by ICT, TLE teachers, and other disciplines.